Social Media Marketing And Quality Of Xiaomi Products - Rini Susilowati (Pusat Riset dan Inovasi Nasional, 2023)
The era of Society 5.0 brings a change to the purchase decision for one activity done at home, As workers, content creators, students, and schoolchildren urgently require a device that is appropriate for their daily demands, the buying decision for one activity done at home, for instance, changes in the era of Society 5.0. Given the widely recognised advantages of Xiaomi products, the company takes advantage of this change in market sales transactions as evidenced by the abundance of fresh creator material that surfaces on social media. The content appears more professional when it has clear camera features, high-quality photos or videos, and 4K video capabilities. Many consumers are purchasing Xiaomi products during a pandemic to meet their current demands. A legitimate company controlled by PT United Media Tbk manufactures the Xiaomi products that are sold in Indonesia. As ratio data must be analysed in this research approach, quantitative research is used to determine the extent of the connection between the variables.